2021
DOI: 10.1111/1750-3841.15593
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the chemical qualities and microstructural changes of Lentinula edodes caused by airborne ultrasonic treatment combined with microwave vacuum drying

Abstract: This study analyzed a new drying method using airborne ultrasound combined with microwave vacuum to study its effect on the quality characteristics and microstructure of dehydrated L. edodes. Ultrasonic treatment resulted in many micropores in the product, forming the sponge effect caused by ultrasonic waves, which can promote the rapid evaporation of water in the product. Samples of Lentinula edodes individuals were dried using four methods: hot air drying (HAD), microwave vacuum drying (MVD), microwave vacuu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…However, polysaccharides obtained by ultrasonic technology are not prone to bubbling, have a small contact area with air, and are not prone to browning, which reduces the degree of the Maillard reaction, so the total sugar loss of USMVD and US + MVD was minimal. Lei et al [33] also drew a similar conclusion that the application of ultrasound could reduce the generation of the Maillard reaction, while increased acoustic energy density could prevent the sugar content in shiitake mushroom from decreasing more than that in the control group. In the dried samples, the protein content was controlled between 5.37% and 5.93%, indicating that MVD with or without ultrasonic treatment had no significant effect on the protein content ( p > 0.05), but the protein content of US3M-TFPs was significantly higher than that of H-TFPs ( p < 0.05).…”
Section: Results and Analysismentioning
confidence: 89%
“…However, polysaccharides obtained by ultrasonic technology are not prone to bubbling, have a small contact area with air, and are not prone to browning, which reduces the degree of the Maillard reaction, so the total sugar loss of USMVD and US + MVD was minimal. Lei et al [33] also drew a similar conclusion that the application of ultrasound could reduce the generation of the Maillard reaction, while increased acoustic energy density could prevent the sugar content in shiitake mushroom from decreasing more than that in the control group. In the dried samples, the protein content was controlled between 5.37% and 5.93%, indicating that MVD with or without ultrasonic treatment had no significant effect on the protein content ( p > 0.05), but the protein content of US3M-TFPs was significantly higher than that of H-TFPs ( p < 0.05).…”
Section: Results and Analysismentioning
confidence: 89%
“…Similar results have also shown that microwave and MV drying time can be reduced for pistachio kernel and f honey by applying US pretreatment (Jahanbakhshi, Kaveh, et al, 2020; Jiang, Bai, Sun, & Zhu, 2020). Lei et al (2021) also reported that ultrasonic combination with MVD could promote the rapid evaporation of water in the Lentinula edodes . At identical ultrasonic power, the accelerated drying rate of US + MVD with US pretreatment was slightly higher than that of US + MD with US pretreatment.…”
Section: Results and Methodsmentioning
confidence: 98%
“…The results of their study showed that the US pretreatment has positive effects on reducing of drying time to dehydrate the samples. The use of ultrasonic combined with drying makes lentinus edodes produce many micropores, forming a sponge effect, which is conducive to the rapid evaporation of water in the product (Lei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…When MD was used to treat P. eryngii, the TPC of P. eryngii slices decreased with increasing microwave power, and the lowest TPC was 28.82 ± 0.50 mg/g. Lei et al (2021) found that after air ultrasonic treatment combined with microwave vacuum drying of lentinus edodes, the retention rate of total sugar could be increased by 25.91% compared with HAD, effectively preventing the reduction of total sugar content.…”
Section: Tpcmentioning
confidence: 98%